Heart Rate Variability During Exercise: A Comparison of Artefact Correction Methods. Issue 3 (March 2018) - Giles, David A.; Draper, Nick
Abstract : Abstract: Giles, DA and Draper, N. Heart rate variability during exercise: a comparison of artefact correction methods. J Strength Cond Res 32(3): 726–735, 2018—There is a need for standard practice in the collection and processing of RR interval data recorded using heart rate monitors (HRMs) in research. This article assessed the validity of RR intervals and heart rate variability (HRV) data obtained using an HRM during incremental exercise and artefact correction methods. Eighteen participants completed an active orthostatic test and incremental running V[Combining Dot Above]O2 max test, while simultaneous recordings using a Polar V800 HRM and an electrocardiogram were made. Artefacts were corrected by deletion; degree zero, linear, cubic, and spline interpolation; and Kubios HRV software. Agreement was assessed using percentage bias, effect size (ES), intraclass correlation coefficients (ICC), and Bland-Altman limits of agreement (LoA). Artefacts increased relative to exercise intensity, to a peak of 4.46% during 80–100% V[Combining Dot Above]O2 max. Correction of RR intervals was necessary with unacceptably increased bias, LoA, and ES and reduced ICC in all but resting recordings. All correction methods resulted in data with reduced percentage bias and ES for resting and <60% V[Combining Dot Above]O2 max recordings. However, at >60% V[Combining Dot Above]O2 max, even with correction, large amounts of variation were present in HRV measures of root mean square of the successive difference of intervals, low-to-high frequency ratio, Poincaré dispersion perpendicular to the axis (SD1), and sample entropy. Linear interpolation produced RR intervals with the lowest bias and ES. However, caution should be given to HRV parameters at high exercise intensities, as large amounts of variation were still present. Recommendations for minimizing artefacts are discussed, along with guidelines for their identification, correction, and reporting. Abstract : Supplemental Digital Content is Available in the Text.